2013
DOI: 10.1007/s11046-013-9650-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of In Vitro Macrophage System to Evaluate Phagocytosis and Intracellular Fate of Penicillium marneffei Conidia

Abstract: Penicillium marneffei is a pathogenic fungus that can cause a life-threatening systemic mycosis in the immunocompromised hosts. We established the model for the phagocytosis of P. marneffei conidia by RAW264.7 murine macrophages and designated the fate of P. marneffei in RAW264.7 cells with respect to persistence, phagosome-lysosome-fusion. And we impaired the immune status of mouse and compared the fate and phagosome-lysosome-fusion of P. marneffei in immunocompetent and immunosuppressed mouse peritoneal macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…A strain of T. marneffei SUMS0152 (IFM52703) was obtained from the Fungi Research Center of Sun Yat-sen Memorial Hospital and the experimental protocol was approved by the Medical Ethics Committee of Sun Yatsen University. 14 The animal studies were reviewed and approved by the Animal Research and Care Committee of Sun Yat-sen University (SCXK Guangdong 2009-0011), and followed the guidelines for the welfare of the laboratory animals (Laboratory animal-Guideline for ethical review of animal welfare, GB/T3589-2009).…”
Section: Materials and Methods Ethical Standardsmentioning
confidence: 99%
See 2 more Smart Citations
“…A strain of T. marneffei SUMS0152 (IFM52703) was obtained from the Fungi Research Center of Sun Yat-sen Memorial Hospital and the experimental protocol was approved by the Medical Ethics Committee of Sun Yatsen University. 14 The animal studies were reviewed and approved by the Animal Research and Care Committee of Sun Yat-sen University (SCXK Guangdong 2009-0011), and followed the guidelines for the welfare of the laboratory animals (Laboratory animal-Guideline for ethical review of animal welfare, GB/T3589-2009).…”
Section: Materials and Methods Ethical Standardsmentioning
confidence: 99%
“…Peritoneal macrophages (pMacs) were collected from the control and immunosuppressed BALB/c mice after the third injection by peritoneal lavage as described. 14 Mouse RAW264.7 macrophages were preserved in the Fungi Research Center of Sun Yat-sen Memorial Hospital.…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, our previous study has found the exact contribution of the acidification of the phagolysosome and the activation of lysosomal enzymes in anti-fungi [19].…”
Section: Introductionmentioning
confidence: 95%
“…P. marneffei conidia were labeled with fluorescein isothiocyanate (FITC) as previously described [19]. MDM were seeded in 6-well plates at a concentration of 1 Â 10 6 cells/ml with and without dexamethasone pretreatment, and infected with P. marneffei conidia at a multiplicity of infection (MOI) of 1:5.…”
Section: Measurement Of Conidia Phagocytosis and Killing By Human Macmentioning
confidence: 99%